Pengaruh Menopause Terhadap Kardiovaskular - Guadelupe Maria Melisa Wiriadinata; Dewa Ayu Agus Sri Laksemi (Journal of Pharmaceutical and Sciences, 2026)
Menopause is the permanent cessation of menstruation for 12 consecutive months without any underlying pathological cause. This occurs due to ovarian follicular atresia, which leads to the cessation of estrogen production. The menopausal transition begins 5 to 10 years before menstruation ceases. During menopause, estrogen levels decline, leading to biological changes in the body, such as an increase in total cholesterol, low-density lipoproteins (LDL), triglycerides, and apolipoprotein B, as well as a decrease in high-density lipoprotein (HDL), an increase in visceral fat, and the development of metabolic syndrome. Various characteristics of menopause have been evaluated in relation to cardiovascular disease (CVD) risk, including age at menopause onset, type and stage of menopause, endogenous estradiol levels, and menopause-related symptoms. These factors have been found to be associated with CVD risk, with the highest risk occurring in women with ovarian failure and relatively early menopause. Women with early menopause (aged 40–44 years) have a hazard ratio of 1.55 (95% CI: 1.38–1.73) for coronary artery disease events compared to women with menopause at age 50–54 years. Women with premature ovarian failure tend to have a shorter life expectancy compared to those who experience late menopause, primarily due to an increased risk of cardiovascular disease.